2017
DOI: 10.5223/pghn.2017.20.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Efficacy of Lidocaine Spray for Sedated Esophagogastroduodenoscopy in Children

Abstract: PurposeOur aim in this study is to investigate efficacy of topical lidocaine spray for sedated esophagogastroduodenoscopy (EGD) in children.MethodsThe endoscopy of children aged between 3-18 years who underwent EGD in our endoscopy unit. Intravenous (IV) midazolam and ketamine were used for sedation. Prior to sedation, endoscopy nurse applied topical lidocaine 10% with pump spray at 1 mg/kg dose in group 1, and distilled water via identically scaled pump spray in group 2, in a double blinded fashion.ResultsSed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The results showed that cumulative propofol requirements in the benzydamine hydrochloride group was significantly less than in the control group. The result is consistent [3,5]. However, lidocaine spray might cause irritation, nausea, vomiting, and dysphagia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The results showed that cumulative propofol requirements in the benzydamine hydrochloride group was significantly less than in the control group. The result is consistent [3,5]. However, lidocaine spray might cause irritation, nausea, vomiting, and dysphagia.…”
Section: Discussionsupporting
confidence: 72%
“…Topical analgesic is often added to reduce throat irritation incidence which can trigger gag reflex when an endoscopic probe is inserted. Combination of propofol and topical analgesic is an alternative to reduce propofol consumption and to provide adequate sedation while avoiding propofol side effects [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Level of agreement: 100% Good evidence shows that combining sedation with oropharyngeal anaesthesia improves tolerance and comfort of gastroscopy. [152][153][154][155] Topical pharyngeal anaesthesia reduces the gag reflex in patients sedated with propofol. 156 However, concerns have been raised as to whether the combination of throat spray and sedation increases the risk of aspiration pneumonia 152 157-159 ; no published evidence is available to substantiate these concerns.…”
Section: There Is No Evidence To Suggest the Combination Of Throat Sp...mentioning
confidence: 99%
“…The combination of sedation with topical anaesthetics in endoscopic procedures is not new and has been tested also in previous studies, where lidocaine in the form of spray or gel was locally applied. 22 However, benzydamine HCl mouthwash is becoming an alternative for this approach in the clinical practice as it can induce lower side effects than lidocaine.…”
Section: The Mechanisms Of Action Of Benzydamine Hclmentioning
confidence: 99%